76.2k views
0 votes
Solve the equation.
y + 3 = -y + 9
A. y = 1
B. y = 3
C. y = 6
D. y = 9

User Wan Chap
by
5.4k points

2 Answers

2 votes
Y=3

y+3-3=-y+9-3

Simplify
y=-y+6

y+y=-y+6+y

2y=6

2y=6
———
2 2

y=3


I hope this helped!!
User JamieJag
by
6.1k points
1 vote

Answer:

B. y = 3

Explanation:

to solve the equation, you need to get y by itself. so, you have to add y to both sides, then subtract 3 from both sides. after that, you divide both sides by 2 and there's your answer.

it'll look like this:

y + 3 = -y + 9

2y + 3 = 9

2y = 6

y = 3

User Frederik Heyninck
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.